Taṣmīm Wasīlah al-Biṭaqah al-Taʻlīmiyah al-Qā’imah ʻala al-Tadaruj al-Taʻlīmi Litʻalum al-Mufradāt ladā al-Ṭulāb żawa al-‘Iʻāqah al-Żihniyyah - Friendis Syani Amrulloh; Wilda Ashfa Nihayah; Assofa Fitryyana; Ruqayyah Ruqayyah; Indah Afifatul Hasanah; Rohmatun Nafiana; Muhammad A’inul Haq (KURAS Institute, 2025)
This study is initiated by the difficulties faced by students with intellectual disabilities in mastering Arabic vocabulary, as well as the reliance on teaching methods that do not comprehensively integrate audio-visual media. This study aims to design and develop educational flashcard media based on scaffolding theory and equipped with a QR code feature for learning Arabic vocabulary at Sekolah Luar Biasa Negeri (SLBN) Sugihwaras Bojonegoro. The researcher adopted the Research and Development (R&D) method following the 4D model, while implementing Single Subject Research (SSR) with an A-B design to compare the baseline phase and intervention phase for each student. The study employed a mixed-methods approach to collect data through observation, interviews, expert validation questionnaires, and pre-test and post-test. The results indicated that the developed media is highly effective, as shown by the increase in the average pre-test score from 83.3 to 96.6 in the post-test, the achievement of an N-Gain value of 0.66 in the medium category, and the improvement and stability of individual student performance. Theoretically, this study contributes to the development of scaffolding-based Arabic vocabulary learning models for students with intellectual disabilities by integrating visual, auditory, and gradual assistance principles within an inclusive education context. Practically, the study offers an adaptive instructional medium that can be used by Arabic teachers in special education settings to improve students’ vocabulary recognition, pronunciation, and learning independence. The study concludes that integrating scaffolding techniques with digital audio-visual media constitutes an effective and sustainable solution for developing language skills among students with special needs.